Critical reappraisal of Balangero chrysotile and mesothelioma risk (Epidemiology, Biostatistics, and Public Health, 2022)
BackgroundBalangero, 40 km northwest of Torino in the Piedmonte Region, was home to the largest and most active chrysotile mine in Europe operating from 1916 - 1990 and employed over 300 men at any one time. The chrysotile was thought to be pure. Despite this some claim it has been responsible for causing numerous mesotheliomas. This report refutes this claim on the grounds that it is not pure but potentially contaminated by tremolite asbestos. In addition there are numerous alternate sources of naturally occurring and commercially available amphibole asbestos in the region.MethodsGeological studies illustrate the presence of naturally occurring tremolite and various analyses have shown naturally occurring and commercially used amphibole its presence in animal and human tissue. The diagnostic criteria used to study pleural disease in the Balangero cohort were examined on a case by case basis.ResultsSeveral authors have searched available registries for post-mortem information and listed possible mesothelioma cases. Cross matching these searches has been attempted and the strength of their diagnoses examined.ConclusionThere is good evidence that crocidolite, amosite and tremolite are responsible for the alleged mesothelioma cases at Balangero. Myriad sources of naturally occurring and commercial amphibole asbestos exist in the region to account for the alleged cases. Regrettably, necessary information is incomplete and insufficient for the cohort which calls the diagnostic accuracy of the cases into question. The problem is further compounded by confusion surrounding job titles and raises the question if any of cases actually ever occurred in ‘miners’ per se.